IMITATION OF STANDARD VOLUMETRIC ACTIVITY METAL SAMPLES - A. I. Zhukouski; A. O. Nichyparchuk; A. A. Khrutchinsky; S. A. Kutsen (Приборы и методы измерений)
Due to the specific character of problems in the field of ionizing radiation spectroscopy, the R&D and making process of standard volumetric activity metal samples (standard samples) for calibration and verification of spectrometric equipment is not only expensive, but also requires the use of highly qualified experts and a unique specific equipment. Theoretical and experimental studies performed have shown the possibility to use imitators as a set of alternating point sources of gamma radiation and metal plates and their use along with standard volumetric activity metal samples for calibration of scintillation-based detectors used in radiation control in metallurgy. Response functions or instrumental spectra of such spectrometer to radionuclides like 137Cs, 134Cs, 152Eu, 154Eu, 60Co, 54Mn, 232Th, 226Ra, 65Zn, 125Sb+125mTe, 106Ru+106Rh, 94Nb, 110mAg, 233U, 234U, 235U and 238U are required for calibration in a given measurement geometry. Standard samples in the form of a probe made of melt metal of a certain diameter and height are used in such measurements. However, the production of reference materials is costly and even problematic for such radionuclides as 94Nb, 125Sb+125mTe, 234U, 235U  etc. A recognized solution to solve this problem is to use the Monte-Carlo simulation method. Instrumental experimental and theoretical spectra obtained by using standard samples and their imitators show a high compliance between experimental spectra of real samples and the theoretical ones of their Monte-Carlo models, between spectra of real samples and the ones of their imitators and finally, between experimental spectra of real sample imitators and the theoretical ones of their Monte-Carlo models. They also have shown the adequacy and consistency of the approach in using a combination of metal scattering layers and reference point gamma-ray sources instead of standard volumetric activity metal samples. As for using several reference point gamma-ray sources with radionuclide like 152Eu, 232Th, 226Ra etc, they allow, in a combination of metal scattering layers, to compensate for the absorption of low energy gamma rays in the metal and to generate the desired response in the backscatter peak range, and finally to get the correct amplitude distribution that is equivalent to interaction effects that occur in the volumetric standard sample with radionuclide uniformly distributed in it.